The EU single market and customs policy: Impact on Estonian foreign trade - Laura Ehrlich (The Research Institute of the Finnish Economy (ETLA), 2002)
Foreign trade is an important mechanism for economic integration with other countries, and plays a significant role in economic growth. The possible impacts of EU membership on Estonian foreign trade have been discussed for years without reaching a clear conclusion. Although the current paper does not purport to offer definitive results, it does shed light on the matter by presenting the main arguments raised by the debate. Using economic theory as a framework for analysis, the paper first discusses the effects of EU membership on the volume and structure of trade, followed by an evaluation of the likely impact on Estonia's trading partners. The majority of the studies surveyed here find that, overall, the trade-creation effect will dominate following EU membership, although trade diversion will occur in sensitive sectors of the economy. However, the magnitude of trade diversion is smaller, the more candidate countries join the EU in the first enlargement wave. The paper also reports that specialization in trade is expected to increase and considers the effect of maintaining trade restrictions on the exports of sensitive sectors to the EU.
Keywords: 330; Eastern Enlargement of the EU; Foreign Trade; Single Market; CEEC; Estonia; EU-Erweiterung; Außenhandel; EU-Binnenmarkt; Osteuropa; Estland